Traditional medicinal practices among the rural people of Tilda, Raipur, India - Parveen3; Sushma Dubey3, *S. Lanjewar1, Rita Luka2, Shaista (International Multidisciplinary Research Journal, 2011)
Due to deforestation and loss of biodiversity natural resources, many valuable herbs are in the verge of extinction. The present paper deals traditional uses of plant species by the rural people of Tilda, Raipur. The claims were gathered by interviewing traditional healers, especially villagers, of the study area. Findings of the study show the increased use of traditional medicine among the natives of the study area.